Error control for non-scalable and scalable video over error-prone networks - Fang, Tao (2008)
Recent advances in technology have resulted in a significant growth in wireless communications. As wireless access becomes more commonplace, the need for reliable transmission of mixed media information, such as speech, text, image and video data, over wireless channels is becoming an increasingly important application requirement. As a result, the study of video transmission over error-prone environment is highly promising. Due to the characteristics of wireless transmission environments, namely low bandwidth and high bit error rate, efficient video transmission becomes challenging and error control must be applied to improve the robustness of the video coder. In the thesis, we firstly give an overview of the strategies that can be adopted to make the video data robust. After that, the proposed error control techniques are introduced, which we believe to be the state-of-the-art technologies for video communications over error-prone networks.